1990
DOI: 10.1577/1548-8675(1990)010<0434:eocife>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Condition Indices for Estimation of Growth of Largemouth Bass and White Crappie

Abstract: We evaluated the ability of three condition indices-condition factor (FC), relative condition (K n \ and relative weight (W r )-to estimate annual growth rates of largemouth bass Micropterus salmoides and white crappies Pomoxis annularis collected during standardized autumn electrofishing and trap-net surveys of Texas reservoirs. Multiple-regression models for estimation of length increments from initial length (at the start of the growing season) and condition indices had R 2 values of 0.63-0.76 for largemout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
2
15
0
2
Order By: Relevance
“…Additionally, mean length is not a good measure of growth because it could be small because of poor growth or high exploitation. Using W r to track CHANNEL CATFISH POPULATIONS populations is complicated by the difficulty of accurately weighing fish in the field (Gutreuter and Krzoska 1994) and this index may not accurately reflect growth rates (Gutreuter and Childress 1990). For this study, W r was correlated with growth increments for 2003 (INC 280 , r ¼ 0.50, P ¼ 0.0001, N ¼ 55 lakes; INC 410 , r ¼ 0.50, P ¼ 0.0001, N ¼ 55 lakes) but not for 2005 (INC 280 , r ¼ 0.26, P ¼ 0.08, N ¼ 48 lakes; INC 410 , r ¼ 0.28, P ¼ 0.06, N ¼ 47 lakes).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Additionally, mean length is not a good measure of growth because it could be small because of poor growth or high exploitation. Using W r to track CHANNEL CATFISH POPULATIONS populations is complicated by the difficulty of accurately weighing fish in the field (Gutreuter and Krzoska 1994) and this index may not accurately reflect growth rates (Gutreuter and Childress 1990). For this study, W r was correlated with growth increments for 2003 (INC 280 , r ¼ 0.50, P ¼ 0.0001, N ¼ 55 lakes; INC 410 , r ¼ 0.50, P ¼ 0.0001, N ¼ 55 lakes) but not for 2005 (INC 280 , r ¼ 0.26, P ¼ 0.08, N ¼ 48 lakes; INC 410 , r ¼ 0.28, P ¼ 0.06, N ¼ 47 lakes).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Fishes of a given age, however, are not necessarily of the same size and thus should not be expected to grow at the same rate (Larkin et al, 1957). Size-specific growth rates (Larkin et al, 1957;Gutreuter & Childress, 1990;Putman et al, 1995) allow more meaningful comparisons between populations than do age-specific growth rates (Osenberg et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Fisheries biologists responsible for Lake Erie walleye were interested in finding an easily measured index that could be used as part of their annual surveys to assess the growth, food consumption and prey availability conditions. Previous studies suggested W r and LSI should be related to growth and feeding of fish (Wege & Anderson 1978; Adams & McLean 1985; Gutreuter & Childress 1990; Willis, Guy & Murphy 1991; Blackwell et al. 2000).…”
Section: Discussionmentioning
confidence: 95%